The Secretion of Streptomyces monbaraensis Transglutaminase From Lactococcus lactis and Immobilization on Porous Magnetic Nanoparticles - Ma, Tiange; Lu, Jiaojiao; Zhu, Jing; Li, Xingjiang; Gu, Hongwei; Montalbán-López, Manuel; Wu, Xuefeng; Luo, Shuizhong; Zhao, Yanyan; Jiang, Shaotong; Zheng, Zhi; Mu, Dongdong (Frontiers in Microbiology, 2019)
Microbial transglutaminase (MTG) from Streptomyces mobaraensis is an important enzyme widely applied in food processing for the improvement of protein properties by catalyzing the cross-linking of proteins. In this work we aimed at improving the production and enabling an easy and efficient purification process from culture supernatants. Thus, recombinant vectors, with either a constitutive promoter (Pp5) or an inducible promoter (PnisA), controlling the expression of the MTG gene fused to the signal peptide of Usp45 (SPusp45) were constructed and then expressed in Lactococcus lactis. After purification, 43.5 ± 0.4 mg/L mature MTG-6His was obtained. It displayed 27.6 ± 0.5 U/mg enzymatic activity cross-linking soy protein isolate effectively. The purified mature MTG was immobilized with magnetic porous Fe3O4 nanoparticles, which improved its activity up to 29.1± 0.4 U/mg. The immobilized MTG maintained 67.2% of the initial activity after being recycled for 10 times. The high production and secretion of functional S. mobaraensis MTG from L. lactis and the magnetic immobilized MTG-6His onto Fe3O4 nanoparticles reported in this study would have potential industrial applications.